Exchange Rate Volatility and Macroeconomic Variables in South Africa - Dagume, Albert Mbulaheni (International Journal of Economics and Financial Issues, 2022)
The significance of the exchange rate in determining a country’s macroeconomic performance is indisputable. Thisstudy investigated the impact of exchange rate volatility on macroeconomic variables in South Africa using time series data from 1979 to 2019. Only six macroeconomic variables have been included in this study: GDP, FDI, growth rate, INFR, INT, and trade openness. These variables were chosen as dependent variables, with real exchange rate volatility as the independent variable. The GARCH model was used to generate real exchange rate volatility, and the Ordinary Least Square regression technique was employed to analyze the relationship between dependent and independent variables in this study. The impact of exchange rate volatility on macroeconomic variables in South Africa was substantiated by this study’s findings. It is also concluded that exchange rate volatility has a positive impact on growth, inflation, and interest rates (INT) while having a negative impact on FDI, GDP, and trade openness (OPENN). The results suggest that to increase trade and foreign direct investment, South African authorities should consider the existence and level of exchange rate volatility as well as the expected effects of the exchange rate on each macroeconomic variable.